Multiobjective Optimization of a Novel Solar Tower-Based Gas Turbine-Driven Multi-Generation Plant With Energy, Exergy, Economic, and Environmental Impact Analysis - Colakoglu, Mert; Durmayaz, Ahmet (ASME International, 2021)
AbstractIn this study, a novel solar tower-based gas turbine-driven multi-generation plant is proposed and analyzed in detail with energy, exergy, economic, and environmental impact analysis. A multiobjective optimization is performed by incorporating all performance indicators simultaneously. The proposed plant consists of an intercooling-regenerative-reheat solarized gas turbine cycle as the primary power cycle of a multi-generation plant for the first time. Two organic Rankine cycles are used to utilize waste heat of intercooling section and exhaust of gas turbine. To produce the multi-generation products of power, cooling, industrial process heating, fresh water, floor heating, green hydrogen, domestic hot water, hot air for food drying, and greenhouse heating, power cycles are integrated with a multi-effect desalination, a double-effect absorption refrigeration cycle, an electrolyzer, a drying hot air unit, a greenhouse heater, and an industrial process heater. A rigorous parametric analysis is performed to reveal the effects of variations of decision variables on the plant performance. At the optimum conditions, energy efficiency, exergy efficiency, average unit product exergy cost, and emission savings values are determined as 57.23%, 40.7%, 0.08315 $/kWh, and 948.7 kg CO2/h, respectively. Moreover, proposed plant can produce 1962 kW power and 3.353 kg/h hydrogen in addition to other utilities with a system cost rate of 0.05134 $/s and 3226 kW exergy destruction rate.